Side wheel steamer SAIDIE loading the stern wheel steamer JOHN REILLY for Kobuk, September 29, 1903 - Nowell, Frank H., 1864-1950 (1903)
Caption on image: S.S. Saidie loading the John Reilly for Kobuk, Sept. 29th '03. Nowell 112 The SAIDIE was built in 1899 by Union Iron Works at San Francisco for the Alaska Commercial Co. She was designed as a towboat to handle fright barges and lighters on the bay between St. Michael and the lower Yukon River. She proved unsuccesful in the work for which she was designed, her deep draft making it impossible for her to negotiate the shallows at the river mouth. Her wheels worked on a shingle shaft, rather than independently, with the result that she required the whole of St. Michael Bay to turn around in. In 1900 she was given a second deck with passenger accommodations and placed on the St. Michael-Cape Nome run for the gold rush. In 1902 she was placed on the mail route between Cape Nome and Kotzebue Sound. On September 4, 1904, she was wrecked off Cape Prince of Wales and was subsequently crushed in the ice and became a total loss.(pg. 49, pg. 101)The JOHN REILLY was wrecked at Cape Blossom, Alaska, on October 13, 1905. (pg. 115) Notes from Gordon Newell, ed., The H.W. McCurdy Marine History of the Pacific Northwest (Seattle: Superior Publishing Co, 1966) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number